Need for Transformative Adaptation in South Asia - Karki, M. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2017)
South Asia region is one of the most vulnerable to climate induced hazards and risks. A recent ADB publication predicts that the region is at risk of losing up to 8.8% GDP due to climate change by the end of the century. Climate change directly or indirectly affects all sectors of economy and livelihoods of nations and communities requiring adaptation, mitigation and disaster risk reduction measures so as to reduce and manage increasing risks and stresses. It is therefore logical that all of the South Asian countries have placed adaptation issues on high priority – many already mainstreaming and integrating climate change risks in their socio-economic development policies, plans and programs. Synergy is also gradually developing among sustainable development, environmental conservation and climate change adaptation including disaster risk reduction. Developing capacity of the closely interwoven socio-agro-ecological systems that prevail in South Asia seem to be the running thread among these three important pillars of human development and nature conservation. Recognizing that climate change is one of the newest drivers of change, this paper describes why the current state of scattered, fragmented and micro scale adaptation work in the region need to scale up and scale-out for building a resilient and prosperous South Asia. Multiple approaches are adopted and practiced to design and implement adaptation programs. Participatory visioning and planning of adaptation goal and action is an accepted practice in South Asia countries that are reflected in most of the community-based and ecosystem based adaptation (CBA and EbA) work being undertaken by governmental, non-governmental and community based agencies. However, these local plans are confined to limited budget, geography, population and scope often aimed at reducing the direct and urgent impacts. Given that climate change impacts are not limited to any administrative, ecological and political boundaries as well as it has slow onset process, there is a need to upscale (vertically to policies and programmes) as well as out-scale (horizontally) to larger areas, population and landscape to make adaptation sustainable and resilient to deal with increasing frequency and severity of climate induced risks and hazards. For a tangible and sustained adaptation impact, emphasis need to be laid on identifying innovative ideas and practices that contribute towards improved ecosystem and social services, help make infrastructures more climate resilient, and human development more sustainable. This way, we can achieve adaptation at scale which can also help achieve transformative adaptation. In fact, scaled-up and scale-out and transformative adaptation work underpin sustainable development and biodiversity conservation that can help South Asian countries achieve both Sustainable Development Goals and Aichi Biodiversity Targets.
Keywords: Vulnerable communities, adaptation, disaster risk reduction, transformative adaptation, diverse of change, sustainable development